Examination of the suitability of collecting in event cognitive processes using Think Aloud protocol in golf - Whitehead, Amy E.; Taylor, Jamie A.; Polman, Remco C. J. (Frontiers in Psychology, 2015)
Two studies examined the use of Think Aloud (TA) protocol as a means for collecting data of cognitive processes during performance in golf. In Study 1, TA was employed to examine if different verbalisation (Level 2 or Level 3 TA) instructions influence performance of high and low skilled golfers. Participants performed 30 putts using TA at either Levels 2, 3, or no verbalization condition. Although Level 3 verbalization produced a higher volume of verbal data than Level 2, TA at either Level 2 or 3 did not impair putting performance compared to no verbalization. Study 2 examined the congruence between data collected via TA at Level 3 and cued retrospective recall of cognitive processes during golf performance. Experienced golfers performed six holes of golf whilst engaging in Level 3 TA. After performance, three semi-structured retrospective interviews were conducted (10 min after performance, 24 h after performance and 48 h after performance). A comparison of the themes identified large discrepancies between the information reported during TA and at interview, with only 38–41% similarity in variables reported to influence decision making on each hole. Both studies suggest TA is a valuable method for recording cognitive processes of individuals during task performance. TA provides richer verbal data regarding decisions than cued retrospective recall, and TA does not negatively impact performance.